Subtitling Strategies of English Indonesian Translation Applied in Toy Story 4 Movie - Ilma Triana; Endang Susilawati; Luwandi Suhartono (International Journal of Learning and Instruction (IJLI), 2023)
Subtitling strategies are needed to translate the subtitles of Toy Story 4 movie to give information about the story to the target language viewer. The research aimed to identify the subtitling strategies and analyze which strategies frequently occurred in the Indonesian subtitle of Toy Story 4. The data were taken directly from the English and Indonesian subtitle text of Toy Story 4. This study used a qualitative approach to describe the results of the analysis of subtitling strategies. In gathering the data, the writer used several steps. They are watching, transcribing, identifying, classifying, and reporting. After evaluating the data, the writer presented the finding using the qualitative method. The collected data were transferred to a table and analyzed using the descriptive qualitative method. The finding of this research was 1337 data. The procedure of analyzing data was done by arranging side by side the original dialogue and subtitle versions in the table. The findings of the strategy analysis consist of translation by paraphrase (10.70%), translation by using the transfer (44.05%), translation by using transcription (1.94%), translation by using dislocation (7.78%), translation by imitation (21.02%), moreover translation by condensation (5.98%), translation by decimation (1.12%), in addition, translation by using deletion (3,74%) and translation by using resignation (3.66%). Based on the result of each strategy, it was found that translation by using transfer was the most used in this study, and decimation was the least used in this study.Â Keywords: Descriptive study, Translation, Movie, Subtitling Strategies